The Effects of Multiple Doses of Lomecel‐B, Longeveron' s Cell‐based Therapy, on Alzheimer's disease: Study Design and Rationale of this Phase 2a Multi‐ center Clinical trial. (20th December 2022) - Ramdas, Kevin N.; Brody, Mark; Herskowitz, Brad; Agronin, Marc; Ruiz, Jorge G; Fuquay, Ana; Rodriguez, Savannah; Mehranfard, Danial; McClain‐Moss, Lisa; Gincel, Dan; Hare, Joshua M.; Oliva, Anthony A.
Abstract: Background: Lomecel‐B is an allogeneic medicinal signaling cell (MSC) formulation under clinical investigation for Alzheimer's disease (AD). We have successfully completed a double‐blinded, placebo‐controlled Phase 1 safety trial, in which Lomecel‐B was found to be safe and tolerable in patients with mild AD, and yielded preliminary evidence supporting potential efficacy. Mechanistically, this included evidence of pro‐vascular and anti‐inflammatory activities. Extending upon these promising results, we present the rationale and design of the next‐phase 2a trial in this program. Method: The primary objective of this double‐blinded, randomized, and placebo‐controlled Phase 2a trial is to evaluate the safety of multiple doses of Lomecel‐B versus a single dose or placebo. Forty‐eight participants will be equally randomized to four study arms, and will receive intravenous infusions at Weeks 0, 4, 8, and 12, and followed up through Week 39 post‐first infusion. Arm 1 will receive four intravenous infusions of placebo. Arm 2 will receive one infusion of low‐dose Lomecel‐B (2.5×10 7 cells) followed by three infusions of Placebo. Arm 3 will receive four infusions of low‐dose Lomecel‐B. Arm 4 will receive four infusions of high‐dose Lomecel‐B (10 8 cells). Enrolled subjects will undergo a multi‐tiered screening process (clinical evaluation, blood‐work, MRI, and PET). Major enrollment criteria are mild AD with confirmatory beta‐amyloid tracer PET, 60‐85 years of age, and a MMSE score of 18‐24. Safety will be monitored by examining vital signs, physical and neurological exams, laboratory tests (hematology, coagulation, blood chemistry, and urinalysis), and neuroimaging. The secondary objectives are to assess the effects of Lomecel‐B on the cognitive function, and pro‐vascular and anti‐inflammatory biomarkers. Exploratory objectives include neurocognitive, neuropsychiatric, quality‐of‐life, activities‐of‐daily‐living, frailty status, and biomarkers assessments. Result: This multicenter phase 2a trial has been allowed to proceed by FDA, is IRB approved, and actively enrolling. Conclusion: This trial is designed to obtain safety and preliminary efficacy data on the effects of a multiple doses of Lomecel‐B on mild AD, with an emphasis on biomarkers related to proposed mechanisms of action (MOAs). We anticipate this trial will have complete enrollment by early 2023, and preliminary safety findings available soon thereafter.